The triumph of painting - Gingeras, Alison, M.; Gingeras, Alison, M.; Saatchi, Gallery; Schwabsky, Barry (London : Jonathan Cape, 2005)
Kippenberger, Martin ; Doig, Peter ; Dumas, Marlene ; Tuymans, Luc ; Immendorff, Jörg ; Nitsch, Hermann ; Richter, Daniel ; Althoff, Kai ; Brown, Cecily ; Dalwood, Dexter ; Raedecker, Michael ; Muntean & Rosenblum ; Tal R ; Meese, Jonathan ; Oehlen, Albert ; Schutz, Dana ; Ackermann, Franz ; Scheibitz, Thomas ; Sasnal, Wilhelm ; Ferris, Dee ; Schoorel, Maaike ; Pickstone, Sarah ; Knobloch, Thoralf ; Silva, Mike ; Ashcroft, Michael ; Ruckhäberle, Christoph ; Ward, Christian ; Stoner, Tim ; David, Enrico ; Joffe, Chantal ; Hellermann, Sophie Von ; Neal, Liz ; Lokiec, Tim ; Myerson, Jin ; Guenther, Andrew ; Swansea, Ena ; Bonacina, Mauro ; Baumgärtel, Tilo ; Skaer, Lucy ; Korner, John ; Monroe, Ian ; Kürten, Stefan ; Weismann, Willem ; Bas, Hernan ; McKenzie, Lucy ; Thorpe, David ; Ziegler, Toby ; Marce, Marta ; Tekinoktay, Evren ; Bedwell, Simon ; Wohnseifer, Johannes ; Havekost, Eberhard ; Margolis, Alisa ; Sugito, Hiroshi ; Furnas, Barnaby ; Rossi, Mario
The Triumph of Painting, The Saatchi Gallery London, 2006-09-12. 2005-07-03.
boek